(untitled) (International Journal of Language, Literacy and Translation, 2025)
The fifteenth and the sixteenth centuries mark a major drift in the literary productions of Bengal. The literary scenario of Bengal was previously dominated by Mangalkavyas which would not allow the formation of romance as a literary genre. In this case the formation of the genre in Medieval Bengal was the credit of the Islamic conquerors. They drifted apart from the traditional notions of literary productions in order to give birth to this new genre, however, its audience did not go beyond the Islamic sects. The subject matters were complex for a good portion of the mass to perceive. It was principally due to the advent of Daulat Kazi and Alaol’s translation of Jaishee’s Padmavat that a bigger section of the audience could connect with Bengali romance. The literary elements nurtured by Alaol in his Padmavati were more acceptable by the local audience. This paper aims at finding how Alaol’s Padmavati as an intercultural text, in the construction of romance utilizes the local literary elements which were more acceptable by the masses of Bengal. Secondly, this paper also aims at finding the ruptures and re-innovations in which romance passes through in the text.